Clinical usefulness of novel tag‐less Agile patency capsule prior to capsule endoscopy for patients with suspected small bowel stenosis. Issue 1 (26th May 2014) - Nakamura, Masanao; Hirooka, Yoshiki; Yamamura, Takeshi; Miyahara, Ryoji; Watanabe, Osamu; Ando, Takafumi; Ohmiya, Naoki; Goto, Hidemi
<x xml:space="preserve">Abstract</x> Background and Aim The Agile patency capsule (PC; Given Imaging Ltd, Yoqneam, Israel) is used as a dummy prior to capsule endoscopy (CE) to avoid retention of the CE capsule. However, impaction of the PC's inner radio frequency identification (RFID) tag in a stricture could cause small‐bowel ileus. Recently, the RFID tag‐less PC was introduced into clinical practice. Herein, we aimed to retrospectively evaluate the usefulness of the tag‐less PC. Methods Of 154 patients who were scheduled to undergo CE, 100 consecutive patients (65%) who underwent PC evaluation were enrolled in the present study. Primary study end point was the retention rate of the CE capsule after successful passage of the PC. Secondary end point was analysis of the significant factors affecting the passage of the PC. Results In total, 87 patients (87%) had bowel patency confirmed by PC evaluation. There was no capsule retention in any of these 87 patients during CE. Abnormal findings were obtained from 60 CE, and 41 patients received new or modified treatment. Multivariate analysis of factors related to the confirmation of patency demonstrated that stenosis on imaging was the most influential factor (P = 0.002, odds ratio 16.387). The results confirmed that passage of the PC depends on stenosis on imaging. Conclusions Use of the tag‐less PC confirmed gastrointestinal tract patency for most of the patients who did not have stenosis on imaging and allowed estimation of the patency for patients who did have stenosis on imaging.